Predicting Self–Confident Behaviour with Implicit and Explicit Self–Esteem Measures. Issue 6 (November 2016) - Krause, Sascha; Back, Mitja D.; Egloff, Boris; Schmukle, Stefan C.
The present research compared the validity of popular direct and indirect measures of self–esteem in predicting self–confident behaviour in different social situations. In line with behavioural dual–process models, both implicit and explicit self–esteem were hypothesized to be related to appearing self–confident to unacquainted others. A total of 127 participants responded to the Rosenberg Self–Esteem Scale, the Multidimensional Self–Esteem Scale, and an adjective scale for measuring explicit self–esteem (ESE). Participants' implicit self–esteem (ISE) was assessed with four indirect measures: the Implicit Association Test (IAT), the name–letter task (NLT), and two variants of an affective priming task, the reaction–time affective priming task (RT–APT) and the error–based affective priming task (EB–APT). Self–confident behaviour was observed in four different social situations: (i) self–introduction to a group; (ii) an ostracism experience; (iii) an interview about the ostracism experience; and (iv) an interview about one's personal life. In general, appearing self–confident to unknown others was independently predicted by ESE and ISE. The indirect measures of self–esteem were, as expected, not correlated, and only the self–esteem APTs—but not the self–esteem IAT or the NLT—predicted self–confident behaviours. It is important to note that in particular the predictive power of the self–esteem EB–APT pertained to all four criteria and was incremental to the ESE measures. Copyright © 2016 European Association of Personality Psychology